Risk factors of deep vein thrombosis of lower extremity in patients undergone gynecological laparoscopic surgery: what should we care - Qing Tian; Meng Li (BMC, 2021)
Abstract Background Deep vein thrombosis (DVT) significantly influences the prognosis of patients. It's necessary to analyze the risk factors for postoperative DVT in patients undergone gynecological laparoscopic surgery. Methods Patients who underwent gynecological laparoscopic surgery from January 1, 2018 to May 31, 2020 were included. The characteristics and clinical data of DVT and non DVT patients were collected and analyzed. Logistic regression analysis was performed to identify the risk factors of DVT in patients undergone gynecological laparoscopic surgery. Results A total of 355 patients undergone gynecological laparoscopic surgery were included, the incidence of postoperative DVT was 11.55%. There were significant differences in the age, hypertension, D-dimer, duration of surgery, intraoperative pneumoperitoneum pressure, duration of days in bed between DVT and non-DVT groups (all p < 0.05), and there were no significant difference in the BMI, diabetes, hyperlipidemia, ASA classification and intraoperative blood transfusion between DVT and non-DVT groups (all p > 0.05). Age > 50 years (OR 4.246, 95% CI 1.234-7.114), hypertension (OR 2.219, 95% CI 1.153-4.591), D-dimer > 0.5 mg/L (OR 3.914, 95% CI 1.083-5.229), duration of surgery ≥ 60 min (OR 2.542, 95% CI 1.101-4.723), intraoperative pneumoperitoneum pressure ≥ 15 mmHg (OR 3.845, 95% CI 1.119-5.218), duration of days in bed > 3 days (OR 1.566, 95% CI 1.182-1.994) was the independent risk factors for DVT in patients undergone gynecological laparoscopic surgery (all p < 0.05). Conclusions The incidence of postoperative DVT in patients undergone gynecological laparoscopic surgery is high, and those high-risk factors should be targeted to intervene in order to reduce the postoperative DVT.